Granulocyte-Colony Stimulating Factor activates JAK2/PI3K/PDE3B Pathway to Inhibit Corticosterone Synthesis in a Neonatal Hypoxic-ischemic Brain Injury Rat Model - Charles, Mélissa S. (Exp Neurol, 2015)
OBJECTIVE: Our previous study demonstrated that granulocyte-colony stimulating factor (G-CSF)-induced neuroprotection is accompanied by an inhibition of corticosterone production in a neonatal hypoxic-ischemic (HI) rat model. The present study investigates how G-CSF inhibits corticosterone production, using adrenal cortical cells and HI rat pups. METHODS: Cholera toxin was used to induce corticosterone synthesis in a rodent Y1 adrenal cortical cell line by increasing cyclic adenosine monophosphate (cAMP). Both corticosterone and cAMP were quantitatively measured using a commercial enzyme-linked immunosorbent assay (ELISA). The downstream signaling components of the G-CSF receptor, including Janus Kinase 2 (JAK2)/Phosphatidylinositol-3-kinase (PI3K)/Protein kinase B (Akt) and Phosphodiesterase 3B (PDE3B), were detected by western blot. Sprague-Dawley rat pups at the age of 10 days (P10) were subjected to unilateral carotid artery ligation followed by hypoxia for 2.5 hours. Brain infarction volumes were determined using 2,3,5-triphenyltetrazoliumchloride monohydrate (TTC) staining. RESULTS: G-CSF at 30ng/ml inhibited corticosterone synthesis but lost its inhibitory effect at higher doses. The inhibitory effect of G-CSF was conferred by interfering with cAMP signaling via the activation of the JAK2/PI3K/PDE3B signaling pathway. The degradation of cAMP by G-CSF signaling reduced corticosterone production. This mechanism was further verified in the neonatal HI brain injury rat model, in which inhibition of PDE3B reversed the protective effects of G-CSF. CONCLUSION: Our data suggest that the neuroprotective G-CSF reduces corticosterone synthesis at the adrenal level by degrading intracellular cAMP via activation of the JAK2/PI3K/PDE3B pathway.